Hydro politics and water wars - Siqqiqui, Iqtidar ([S.l.] : Vanguard,Pakistan, 2013)
Water is an important input to irrigated agriculture. In Pakistan unfortunately, it is fast becoming a diminishing resource due to many reasons including global warming. To meet present and future requirements, water should be conserved in the country at as many places as possible. However, politics of water is not allowing it to happen. Hydro-Politics in Indus River Basin by Iqtidar H. Siddiqui is a comprehensive commentary on the management and utilization of Indus River system waters both internationally and domestically and describes the Hydro-Political forces, which do not permit advancement in water sector in the country. The book infect gives a 'wake-up call' to the country in view of diminishing water resources, expected 'water disaster' due to climate change and hydro-political forces in the country.
Keywords: India; Pakistan; Water-supply--Management; Water-supply--Political aspects